Government "underspending" in perspective: Incompetence, inertia, or indigestion? - Toby C. Monsod (University of the Philippines, School of Economics (UPSE), 2016)
The measured underspending over the last 5 years has more to do with ambitious targets rather than apathetic or incompetent bureaucrats: while actual disbursements fell short of planned disbursements by about ten percent per year from 2011 to 2015, real per capita disbursements on capital outlays and maintenance and operating expenses increased relative to levels in 1999 to 2010 by an average of 41.6 and 76.8 percent respectively. The bureaucracy was unable to keep up with its own ambitions because of absorptive capacity constraints which were driven in part by the inertia from three decades of maneuvering in tight fiscal space as well as coordination problems and other structural bottlenecks, some of which have long-attended budget and plan design and execution but have not been recognized as binding constraints until now. The fund absorption problem is not uniform across agencies however indicating more fundamental organizational issues in certain sectors, and the need for actions beyond public finance management reforms to optimize the contribution of fiscal spending to inclusive growth.
Keywords: 330